Variation in electron work function with temperature and its effect on the Young's modulus of metals. (1st April 2015) - Rahemi, Reza; Li, Dongyang
Abstract : Properties of metals are fundamentally determined by their electron behavior, which is largely reflected by the electron work function ( φ ). Recent studies have demonstrated that many properties of metallic materials are directly related to φ, which may provide a simple but fundamental parameter for material design. Since material properties are affected by temperature, in this article a simple model is proposed to correlate the work function with temperature, expressed as φ ( T ) = φ 0 - γ ( k B T ) 2 φ 0, where γ varies with the crystal structure. This φ - T relationship helps determine and explain the dependence of metal properties on temperature on a feasible electronic base. As a sample application, the established relationship is applied to determine the dependence of the Young's modulus of metals on temperature. The proposed relationship is consistent with experimental observations.